Development of a Website-Based Activity and Cash Information System for Mosque Management: A Case Study of Al-Hikmah Mosque: Pengembangan Sistem Informasi Kegiatan dan Kas Berbasis Website untuk Pengelolaan Masjid: Studi Kasus di Masjid Al-Hikmah - Aji, Bagas Prakoso; Findawati, Yulian (Universitas Muhammadiyah Sidoarjo, 2023)
This research focuses on the development of a website-based activity and cash information system for mosque management, aiming to overcome the inefficiency of using printed pamphlets for announcing religious activities. The study adapts the waterfall development model to design the system, with questionnaire testing using a Likert scale to evaluate the system's effectiveness. The case study was conducted at Al-Hikmah Mosque in Sidoarjo, involving 8 mosque administrators and 2 mosque imams. The results indicated that the software functions as expected, providing an efficient and accurate means of disseminating mosque activity and cash information, reducing the need for manual notifications. The system received a total score of 72.25% and was considered eligible for use. Highlights: Mosques serve as important centers for Islamic da'wah and religious activities. Traditional methods of announcing activities, such as printed pamphlets, can be costly and inefficient. The development of an activity and cash information system can help mosques streamline their communication and financial management processes.